Citizen Subject : Foundations for Philosophical Anthropology - Balibar, Étienne, 1942- (Book collections on Project MUSE., 2017)
This book constitutes the summation of Étienne Balibar's career-long project to think the necessary and necessarily antagonistic relation between the categories of citizen and subject.